2014
DOI: 10.1021/bi401523b
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Modification, Dehydration, and Molecular Crowding Effects on the Thermodynamics of i-Motif Structure Formation from C-Rich DNA

Abstract: DNA sequences with the potential to form secondary structures such as i-motifs (iMs) and G-quadruplexes (G4s) are abundant in the promoters of several oncogenes and, in some instances, are known to regulate gene expression. Recently, iM-forming DNA strands have also been employed as functional units in nanodevices, ranging from drug delivery systems to nanocircuitry. To understand both the mechanism of gene regulation by iMs and how to use them more efficiently in nanotechnological applications, it is essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
101
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(107 citation statements)
references
References 48 publications
(104 reference statements)
5
101
1
Order By: Relevance
“…Given our 16 , and others’, 17, 18 data on the effect of PEG on iM pK a , we investigated the difference between the pH determined by electrode measurement and the activity of protons in the PEG solutions as detected by small molecules. We examined five well-known pH indicators and cytidine monophosphate by monitoring the change in UV-Vis absorbance with change in pH in 30 mM sodium cacodylate buffer with and without 40% PEG-300.…”
Section: Resultsmentioning
confidence: 99%
“…Given our 16 , and others’, 17, 18 data on the effect of PEG on iM pK a , we investigated the difference between the pH determined by electrode measurement and the activity of protons in the PEG solutions as detected by small molecules. We examined five well-known pH indicators and cytidine monophosphate by monitoring the change in UV-Vis absorbance with change in pH in 30 mM sodium cacodylate buffer with and without 40% PEG-300.…”
Section: Resultsmentioning
confidence: 99%
“…Some stabilization of the i‐motif at neutral pH was observed, but these results were obtained for short tetrameric structures and are difficult to extrapolate to biologically relevant intramolecular i‐motifs. As cytidine is subject to epigenetic modifications, the presence of 5‐methyl‐C and 5‐hydroxymethyl‐C in the C‐rich telomere sequence has been studied, thus showing small changes in the stability of the modified i‐motifs . Interestingly, it has been observed that the inclusion of ribocytidines destabilizes i‐motifs, but arabino‐cytidines have the opposite effect .…”
Section: Discussionmentioning
confidence: 99%
“…Base modifications such as 5‐methylcytosine and 5‐hydroxymethylcytosine are permissive bases that can be adapted to i‐motif structures. They show position‐dependent stability and different behavior under experimental crowding conditions . These bases are important epigenetic markers in the human genome.…”
Section: Introductionmentioning
confidence: 99%
“…15 Nevertheless, only a few studies reported the i-motif folding at neutral pH. [16][17][18] In this study, we hypothesized that the intra-strand cross-link in the i-motif structure might increase its stability in terms of both pH-dependency and thermal denaturation. We have already reported the 4-vinyl-substituted analog of thymidine (T-vinyl) as an efficient cross-linking nucleobase for adenine and thymine in the close proximity of the target strand.…”
mentioning
confidence: 89%
“…15 Nevertheless, only a few studies reported the i-motif folding at neutral pH. [16][17][18] In this study, we http://dx. …”
mentioning
confidence: 90%